(untitled) (Nativa, 2026)
Critical N-NO3- and chlorophyll levels in lettuce leaves grown hydroponically under forced air pressure ABSTRACT: The production of lettuce (Lactuca sativa L.) under hydroponic systems in the Mantaro Valley requires optimal nitrogen (N) levels to meet quality standards established by the EU Commission Regulation. This study was conducted in the greenhouse of the El Mantaro Agricultural Experimental Station, Jauja, Peru, to determine the critical levels of N-NO3- in petiole sap, in lettuce leaves (cv. Seda), and foliar chlorophyll, as well as identifying the N concentration in the nutrient solution that maximizes yield without exceeding the permissible limits of N-NO3-. Treatments of 0.5, 1, 4, 7, 10, 13, 16, 19, and 22 mmol N L-1 were applied, with six replications. Results indicated that the optimal N concentration in the nutrient solution ranged between 1.25 and 4.0 mmol N L-1, significantly improving crop growth, yield, and quality. The critical levels of N-NO3- were 3347.43 mg kg-1 in fresh leaves, 482.54 mg L-1 in petiole sap, and 2.12 µg g-1 on chlorophyll, complying with the maximum limit of 4500 mg kg-1 of N-NO3- in fresh weight. This study contributes to optimizing nitrogen fertilization in hydroponic systems, ensuring product quality and food safety. Keywords: nitrate; Savia; quality; production; nutrition. RESUMEN: La producción de lechuga (Lactuca sativa L.) en sistema hidropónico en el Valle del Mantaro requiere niveles óptimos de nitrógeno (N) para cumplir con los estándares de calidad establecidos por el Reglamento de la Comisión UE. Este estudio se desarrolló en el invernadero de la Estación Experimental Agropecuaria El Mantaro, Jauja, Perú; con el objetivo de determinar los niveles críticos de N-NO3- en la savia del peciolo, en hojas de lechuga variedad Seda y clorofila foliar, así como identificar la concentración de N en la solución nutritiva que maximiza la producción sin superar los límites permisibles de N-NO3-. Se aplicaron tratamientos con 0,5, 1, 4, 7, 10, 13, 16, 19 y 22 mmol N L-1, con seis repeticiones. Los resultados indicaron que la concentración óptima de N en la solución nutritiva se sitúa entre 1,25 y 4,0 mmol N L-1, lo que mejora significativamente el crecimiento, la producción y la calidad del cultivo. Los niveles críticos de N-NO3- fueron 3347,43 mg kg-1 en hoja fresca, 482,54 mg L-1 en la savia del pecíolo y 2,12 µg g-1 en clorofila, cumpliendo con el límite de 4500 mg kg-1 de N-NO3- en peso fresco. Este estudio contribuye a optimizar la fertilización nitrogenada en hidroponía, asegurando la calidad y la seguridad alimentaria. Palabras clave: nitrato; savia; calidad; producción; nutrición.